If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -126 = 6(8x + 3) Reorder the terms: -126 = 6(3 + 8x) -126 = (3 * 6 + 8x * 6) -126 = (18 + 48x) Solving -126 = 18 + 48x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48x' to each side of the equation. -126 + -48x = 18 + 48x + -48x Combine like terms: 48x + -48x = 0 -126 + -48x = 18 + 0 -126 + -48x = 18 Add '126' to each side of the equation. -126 + 126 + -48x = 18 + 126 Combine like terms: -126 + 126 = 0 0 + -48x = 18 + 126 -48x = 18 + 126 Combine like terms: 18 + 126 = 144 -48x = 144 Divide each side by '-48'. x = -3 Simplifying x = -3
| x=7+4(y-3) | | -8a-3a=-22 | | 4n-3n=-7 | | 14+10A=44 | | -n+8n=21 | | (3x-1)(2x+4)=0 | | 33-7n=8(1-4n) | | 6x^2+1=12 | | -37-52=11z-85 | | 1-3v+1=2 | | x.2-8x-20=0 | | -3x-x=4 | | 21+7x=7(6x-7) | | 6m-7=8m+19 | | 3(x+4)=-2(x-7)-15 | | 7x=8x-6 | | 14-2x=2(7-x) | | 45x-36y=180 | | -37=-1+3(3n-3) | | x^3+x^2-56x=0 | | x^2+4x+17= | | -36=-1+3(3n-3) | | 5x+2=x+(2x-10) | | .6u+2=6 | | Y=16+.4(62) | | 2x^2+2x=-8x-12 | | 2x-1=-7x-1 | | -27-x^2=0 | | (-80)+33= | | 2(x+3)-4(x+9)=6(x+7) | | -3(3-3a)=-36 | | Y=16+.4(x) |